Using “Book Creator” Application in Making e-Modules as Teaching Material for English TOEFL Courses - Fitria, Tira Nur (Institut Teknologi Bisnis AAS Indonesia, 2024)
This study simulates the use of Book Creator application in making and designing e-module of the material TOEFL courses. This research is descriptive qualitative research. The result analysis shows that e-module can be created in Book Creator. We can open Chrome browser then type book creator.com on the search page. If the book creator has opened, click Create Free Account. We click “New Book”. The e-book size display will appear. The first page (cover) of e-book will be opened. On the right side of the cover there is a “+”, “i” icon and a triangular-shaped play icon. Next select the “+” icon and click “shapes” to create a second color background on the e-book page. We can select the “+” icon to add content to the page. We can select